Investigation of the refined safety factor for berthing energy calculation - Kim, S.W. (Techno-Press, 2020)
As the growth of world trade has surged rapidly over the past years, the number is expected to continue growing over the coming years. Although the transportation costs can be reduced by using larger vessels, however, new berthing structures have to be constructed in order to cater for the larger vessels. This leads to a need for researching on designing a better berthing structure. For optimization of berthing structure design, we need to provide a better estimation of berthing energy than the previous methods in the existing guidelines. In this study, several berthing parameters were collected from previous works and researches. Moreover, the scenarios were selected efficiently by using a sampling technique. First, the berthing energy was calculated by executing 150 numerical simulations. Then, the numerical simulation results were compared with the results calculated by existing methods quantitatively to investigate the sensitivity of the berthing parameters and the accuracy of existing methods. The numerical method results have shown some deviation with respect to the existing method results in which the degree of deviation varies with the methods and the tendency of differences is dependent on certain berthing parameters. Then, one of the existing methods which has shown a small deviation was selected as a representative method and applied with several safety factors to obtain a suitable safety factor for the design. Copyright Â© 2020 Techno-Press, Ltd.